Economic geography of the U.S.S.R. - Baranskij, N. N. (Nikolaj Nikolaevič), 1881-1963; Belskij, S. (Moscow : Foreign Languages Publishing House, 1956)
Boek geeft een economisch geografisch beeld van de USSR.